(untitled) (Colloquia Comparativa Litterarum, 2025)
The essay presents two ideas. First, the philosophical-aesthetic category of the dystopian-utopian is the basis of the literary-philosophical genre of dystopia-utopia in classical socio-political works. And second, it outlines some features of the genres dystopia utopia and dystopia. The first idea is derived from European critical philosophy. The second is based on Plato, mostly on the Republic, a work that serves as a starting point for the analysis of the dystopia-utopia and dystopia genres. Classical and more recent works, some of which have not been examined as dystopia-utopia, illustrate these theoretical ideas. The essay pays particular attention to the novels Resurrection by Tolstoy and Bend Sinister by Nabokov.